THE EFFECTIVENESS OF E-JOBSHEET USING FLIP PDF PROFESSIONAL APPLICATION IN THE COURSE OF ROAD PAVEMENT CONSTRUCTION - Ismon, Asrizal; Putri, Prima Yane (Jurnal Applied Science in Civil Engineering, 2023)
The constraint in the course "Road Pavement Construction" is the insufficient availability of teaching hours during the practical sessions. This research was conducted with the aim of evaluating the extent of effectiveness in implementing educational materials using the Flip PDF Professional application in the context of teaching the course of road pavement construction. The study employed a quasi-experimental design as its research approach. Data were collected through the use of tests, comprising a pretest and a posttest. The evaluation in this study was conducted in two phases, namely the initial phase and the final phase. The pretest phase was used to measure the similarities between the two groups, while the posttest phase was used to measure the learning outcomes' progress. According to the results of this research, Flip PDF Professional exhibited an efficiency rate of 62.07% in the course of road pavement construction, which falls under the moderately effective category. In specific situations such as during the Covid-19 pandemic, the use of alternative learning tools like e-jobsheets with the Flip PDF Professional application in the course of road pavement construction becomes relevant.